Antioxidant and antiangiogenic potential of kebiul (Caesalpinia bonduc (L) Roxb.) from South Bengkulu as a chemopreventive agent - Wulandari, Septi; Wibowo, Risky Hadi; Nurwidiyani, Ria; Hayati , Risda; Nadia; Putri , Amey (Jurnal Ilmiah Farmasi, 2026)
Background: Kebiul seeds are an Indonesian medicinal plant with potential antioxidant and chemopreventive properties against cancer. The development, growth, and invasion of malignant cancer closely link to angiogenesis, which antioxidant effects can influence.Objective: This study aims to evaluate the antioxidant activity of kebiul seeds based on the IC50 and their anti-angiogenesis effects.Method: Extraction was performed using the maceration method using ethyl acetate, n-hexane, and ethanol. The anti-angiogenesis test was conducted using the chorioallantoic membrane (CAM) method, while the antioxidant activity was assessed using the diphenylpyrrolhydrazyl (DPPH) method.Results: The finding revealed the antioxidant activity values, as indicated by the IC50, were 45.225 ppm for the ethanol extract (strong antioxidant), 86.190 ppm for the n-hexane extract (strong antioxidant), and 146 ppm for the ethyl acetate extract (medium antioxidant). Anti-angiogenesis tests were conducted across various solvents and concentrations. Significant anti-angiogenesis effects were observed at concentrations of 10, 50, and 1000 ppm. The n-hexane extract yielded average scores of 0.33, 0.66, and 1.3, indicating a good effect. The ethyl acetate extract had average scores of 0.33, 0.5, and 0.66, suggesting a weak effect, while the ethanol extract showed mean scores of 1.33, 1.66, and 2, indicating a strong effect. Conclusion: Ethanol extract demonstrates the most potential as a chemopreventive agent.